Implementasi Extreme programming Pada Website Marketplace Lapak Petani Online - Perdana Wanti, Linda; Fadillah, Fadillah; Ndaru Ikhtiagung, Ganjar; Aditya Pangestu, Ilham (Infotekmesin, 2021)
The use of information technology to improve people’s welfare has been implemented in various lines of life, including selling agricultural products through the marketplace to expand marketing and increase sales figures. Marketplace built based on the website using extreme programming (XP) method. The selection of extreme programming for marketplace development is tailored to all user needs and system requirements because website development is done in a relatively short time and many changes occur during website development. The stages of the extreme programming method are carried out in several iterations to get feedback from the end-users who are used in the website improvement process so that at the end of the iteration process the website developed is in accordance with the needs of the end-user. The output generated from this research is the farmer’s stall marketplace website that is used to market agricultural products from the Cilacap Holtikultura Farmers Association (PHC).